2008
DOI: 10.1111/j.1462-5822.2007.01073.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 matrix protein p17 binds to monocytes and selectively stimulates MCP-1 secretion: role of transcriptional factor AP-1

Abstract: SummaryHIV-1 matrix protein p17 activates a variety of cell responses which play a critical role in viral replication and infection. Its activity depends on the expression of p17 receptors (p17R) on the surface of target cells. Whether p17 also plays a role in stimulating human monocytes, a major HIV-1 reservoir, is not known. Here we show that human monocytes constitutively express p17Rs and that p17 selectively triggers these cells to produce MCP-1. The effect of p17 on MCP-1 expression was observed at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 49 publications
0
43
0
Order By: Relevance
“…Blood was collected from healthy donors, who gave informed consent for this research according to the Declaration of Helsinki. Human monocytes were isolated from whole blood as previously described (7). Primary B lymphocytes were isolated by negative selection from peripheral blood mononuclear cells obtained from healthy donors using the B cell isolation kit II from Miltenyi Biotec according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood was collected from healthy donors, who gave informed consent for this research according to the Declaration of Helsinki. Human monocytes were isolated from whole blood as previously described (7). Primary B lymphocytes were isolated by negative selection from peripheral blood mononuclear cells obtained from healthy donors using the B cell isolation kit II from Miltenyi Biotec according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…It is released in the extracellular space from HIV-1-infected cells and is easily detected in the plasma and tissue specimens of patients (2,3), including those successfully treated with highly active antiretroviral therapy) (4). Extracellularly, p17 has been found to deregulate the biological activities of many different cells that are directly or indirectly involved in AIDS pathogenesis (3,(5)(6)(7)(8)(9)(10). All p17 activities occur after interaction between the functional epitope (AT20) located at the N-terminal region (amino acids 11 to 30) of the viral protein with receptors expressed on different target cells (5).…”
mentioning
confidence: 99%
“…[15][16][17][18] Experiments performed on human primary monocytes have shown that p17 exerts a chemokine-like activity. This activity was mediated by p17 binding to chemokine (C-X-C motif) receptor-1 (CXCR1), and the viral protein was found to mimic some of the interleukin-8 (IL-8) biological activities.…”
mentioning
confidence: 99%
“…Several studies reported JNK activation by a number of viruses, including human immunodeficiency virus type 1 (HIV-1) (31), herpes simplex virus (30), influenza virus (26), adenovirus (27), varicella-zoster virus (48), and Kaposi's sarcoma-associated herpesvirus (35). The activity of JNK has been linked to virus replication mainly through the effect of AP-1 on transcriptional regulation of viral genes (26)(27)(28)42). Other observations linked JNK inactivation with a reduction in the number of herpesvirus genome copies, suggesting that JNK may play a role at a step before the start of viral replication (9,35).…”
mentioning
confidence: 99%